2023
DOI: 10.1182/blood.2022019240
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the immune microenvironment in Waldenström Macroglobulinemia via halting the CD40/CD40-ligand axis

Abstract: Recent investigations have improved our understanding of the molecular aberrations supporting Waldenström Macroglobulinemia (WM) biology; however, whether the immune microenvironment contributes to WM pathogenesis remains unanswered. We first showed how a transgenic murine model of human-like lymphoplasmacytic lymphoma/WM exhibits an increased number of regulatory T (Treg) cells with respect to control mice. These findings were translated into the WM clinical setting, where the transcriptomic profiling of WM p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…We showed here that Tregs from MW-like tumours overexpressed the anti-inflammatory cytokines IL-10 and IL-6. This is in agreement with a recent study showing, in another mouse model and in patient, the existence of a Treg-mediated immunosuppressive phenotype in WM [28]. We also discovered in our mouse model, in comparison to control mice, an expansion of TIM-3 + Tregs cells which secreted higher amounts of immunosuppressive IL-6 and IL-10 cytokines than do TIM-3 -Tregs.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We showed here that Tregs from MW-like tumours overexpressed the anti-inflammatory cytokines IL-10 and IL-6. This is in agreement with a recent study showing, in another mouse model and in patient, the existence of a Treg-mediated immunosuppressive phenotype in WM [28]. We also discovered in our mouse model, in comparison to control mice, an expansion of TIM-3 + Tregs cells which secreted higher amounts of immunosuppressive IL-6 and IL-10 cytokines than do TIM-3 -Tregs.…”
Section: Discussionsupporting
confidence: 94%
“…Targeting this population would then be a therapeutic prospect for WM. In this sense, Sacco et al propose to target the CD40/CD40L axis after having identified its role in the WM cell-Tregs interaction [28].…”
Section: Discussionmentioning
confidence: 99%
“…2G ), rather than naïve cells primed by vaccine. Recent studies have suggested that Treg cells create an immunosuppressive milieu in WM, the most common subtype of LPL 69 . However, we observed no obvious changes in frequencies or signaling pathways in Treg that would suggest an effect of vaccination on this subpopulation ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular and cytogenetic investigations can highlight characteristic chromosomal anomalies with both diagnostic, prognostic, and/or predictive significance. For example, the discovery that an activating mutation of MYD88 is associated with most cases of lymphoplasmacytic lymphoma has made it possible to develop an allele-specific PCR method useful for better understanding this neoplasm, which often presents with clinical and histopathological characteristics which overlap with other forms, such as MZL [ 19 , 20 ]. It should be underlined that molecular genetic tests must always be integrated into clinical, laboratory, and histopathological diagnostics since no molecular alteration in indolent lymphomas is pathognomonic of a single nosological entity [ 21 ].…”
Section: Indolent B-cell Lymphomasmentioning
confidence: 99%